Três ensaios sobre o setor de saneamento básico: tecnologia de produção e eficiência, demanda e regulação econômica - Melo, José Airton Mendonça de (2005)
The first essay estimates a stochastic translog cost frontier function to Brazilian sanitation enterprises. We intent to verify the properties inherent to the technology production and to estimate the technical inefficiency level present in this industry. It is found the occurrence of decreasing return to scale and that household metering and expenses share on total costs constitute the key determinants of the sector's inefficiency. The second essay estimates residential water demand functions taking into account the block rate pricing schedule usually set by water utilities. The progressive pricing, although preserves the convexity property on the budget set, induces the consumer budget constraints be non-linear, what violates the classical assumption of heterogeneity of the explanatory variables required by the ordinary least squares method. An important conclusion is that price elasticity of water consumption is close to unitary. Finally, the third essay aims to set up the price-quantity pair that maximizes welfare in the basic sanitation, preserving finance sustainability in this sector. Technical constraints on systems of water and seweager make the sanitation enterprises operate under a monopoly regime. The solution to prevent the abuse of market power by this regime would be the price regulation by marginal cost, however, this solution does not guarantee finance sustainability. The main conclusion is that any scheme of tariff adjustment requires previously to take steps to reduce the high economic inefficiency observed in this industry.